Text Messaging Based Obesity Prevention Program for Parents of Pre-Adolescent African American Girls - Chishinga Callender; Deborah Thompson (MDPI AG, 2017)
African American girls are at a greater risk of obesity than their nonminority peers. Parents have the primary control over the home environment and play an important role in the child obesity prevention. Obesity prevention programs to help parents develop an obesity-preventive home environment are needed. The purpose of this study was to collect formative research from parents of 8-10-year old African American girls about perceptions, expectations, and content for a text messaging based program. Mothers (n = 30) participated in surveys and interviews to inform message development and content. A professional expert panel (n = 10) reviewed draft text messages via a survey. All the mothers reported owning a cellphone with an unlimited texting plan, and they used their cellphones for texting (90.0%) and accessing the Internet (100.0%). The majority were interested in receiving text messages about healthy eating and physical activity (86.7%). Interviews confirmed survey findings. One hundred and seven text messages promoting an obesity-preventive home environment were developed. The expert panel and parents reported positive reactions to draft text messages. This research provides evidence that mobile health (mHealth) interventions appeal to parents of African American girls and they have ready access to the technology with which to support this approach.